The photoevaporation of a neutral structure by an EUV+FUV radiation field - Lora, Verónica; Vasconcelos, M. J.; Raga, Alejandro C.; Esquivel, A.; Cerqueira, A. H. (Arxiv, 2013)
The EUV photoionizing radiation and FUV dissociating radiation from newly born stars photoevaporate their parental neutral cloud, leading to the formation of dense clumps that could eventually form additional stars. We study the effects of including a photodissociating FUV flux in models of the fragmentation of a photoevaporating, self-gravitating molecular cloud. We compute 3D simulations of the interaction of an inhomogeneous, neutral, self-gravitating cloud with external EUV and FUV radiation fields, and calculate the number of collapsing clumps and their mass. We find that the presence of an outer photodissociation region has an important effect on the formation of dense structures due to the expansion of an HII region. In particular, including a FUV field leads to the earlier formation of a larger number of dense clumps, which might lead to the formation of more stars.